2005
DOI: 10.1056/nejmcp043511
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation after Stroke

Abstract: A 66-year-old man was suddenly unable to speak, follow directions, or move his right arm and leg. He received tissue plasminogen activator within 90 minutes. Four days later, his speech was limited to effortful answers of yes or no. He could not walk or use his right arm, and self-care tasks required maximal assistance. What advice would you offer him and his family regarding rehabilitation for his disabilities? THE CLINICAL PROBLEMApproximately 400 persons per 100,000 population over the age of 45 years have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
469
0
53

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 731 publications
(545 citation statements)
references
References 61 publications
2
469
0
53
Order By: Relevance
“…Physical rehabilitation is the most common post-troke intervention. Rehabilitation can yield some functional gains, but recovery is often incomplete and the majority of patients are left with chronic disability [52][53][54]. Motor networks in surviving peri-infarct regions, as well as the undamaged contralateral homotopic cortex and subcortical structures, demonstrate significant reorganization after stroke [55][56][57].…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
“…Physical rehabilitation is the most common post-troke intervention. Rehabilitation can yield some functional gains, but recovery is often incomplete and the majority of patients are left with chronic disability [52][53][54]. Motor networks in surviving peri-infarct regions, as well as the undamaged contralateral homotopic cortex and subcortical structures, demonstrate significant reorganization after stroke [55][56][57].…”
Section: Preclinical and Clinical Studies For Ischemic Strokementioning
confidence: 99%
“…Cerebrovascular stroke is the most frequent cause of acquired disability in adulthood and among the fastest growing cost factors in the health system (Dobkin, 2005). As a consequence, much attention is devoted to effective rehabilitation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Global aphasia has also been shown to bring an unfavorable prognosis to post-stroke mobility recovery 16 ; this could be phylogenetically related to the simultaneous development of language networks and motor gesture activity in earlier primates 17 . On the other hand, former studies have shown that the nondominant hemisphere for language has a critical role in the recovery of aphasia, probably related to the lexical learning itself present in healthy subjects and to mechanisms of brain plasticity 3,11,18,19 ; recruitment of networks in the nondominant hemisphere is believed to occur concurrently with attempts to repair the damaged original language networks in aphasic patients 3,11,18 .…”
Section: Resultsmentioning
confidence: 99%
“…[1] A brief history of the acute symptoms had to be reported by the patient (whenever possible) or a relative, including data on cardiovascular risk factors and socialeducational information, along with a complete neurological exam and a succinct assessment for hearing impairment (listening to finger-scratching with closed eyes, in each ear at once) and visual acuity; [2] Patients were then tested for attentional deficits by means of the "A" Random Letter Test 7 , being required to tap the unimpaired hand on the desk immediately after hearing the letter "A" (75 letters were orally presented by the examiner, 20 of them were "A" letters); [3] Handedness was assessed according to a fivepoint scale of the Edinburgh Inventory 8 for performance in writing, tooth-brushing, catching food with a spoon, opening a box, drawing, using a knife without fork, sweeping the floor (upper hand on the broomstick), throwing a ball, holding scissors, and striking a match; [4] Visual perception was tested by showing the patients ten abstract figures in several levels of difficulty, each of them displayed for ten seconds, soon after which they would have to point to it among four other figures (scored as hit-or-miss) 9 ;…”
Section: Methodsmentioning
confidence: 99%